Penerapan Akuntansi Berbasis Akrual Dengan Menggunakan Aplikasi SAIBA Pada Kementerian Sosial RI - Desmawan, Deris; Nofianti, Nana (Universitas Labuhanbatu, 2024)
The writing of this Final Project aims to find out how the Application of Accrual-Based Accounting using the SAIBA Application, what are the obstacles in implementing accrual-based accounting at the Ministry of Social Affairs of the Republic of Indonesia. The method used is descriptive and obtained through field studies. The results of the observations obtained by the author in the application of accrual-based accounting using the SAIBA application at the Ministry of Social Affairs of the Republic of Indonesia are in accordance with Government Accounting Standards, and must be maintained because it makes it easier to compile financial statements, and can be seen in more detail the type of realization in detail. The ability of Human Resources in understanding the system for compiling financial reports is already owned by each security guard, but employees who do not have a background in accounting or economics can take advantage of application training. This also prevents the disconnection of knowledge about the preparation of financial statements. It is expected to monitor the SAIBA application regularly so that all problems in the SAIBA application are corrected and refined in order to present financial reports that produce more accurate and accountable information.